Spatial variation and risk assessment of trace metals in water and sediment of the Mekong Delta. (July 2017) - Strady, Emilie; Dinh, Quoc Tuc; Némery, Julien; Nguyen, Thanh Nho; Guédron, Stéphane; Nguyen, Nhu Sang; Denis, Hervé; Nguyen, Phuoc Dan
Abstract: The Mekong Delta, is home to 17 million inhabitants and faces numerous challenges relating to climate change, environmental degradation and water issues. In this study, we assess trace metals concentrations (Al, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Mo, Cd, Hg, Pb) in the water, suspended particulate matter and surface sediments of the Tien River, the Northern branch of the Mekong Delta, during both dry and rainy seasons. Metal concentrations in the dissolved and suspended particle phases remain in the low concentration range of the main Asian Tropical River. During transportation in the riverine part, we evidenced that V, Cr, Co, As and Pb are dominant in the particulate phase while Mo, Ni and Cu dominate in the dissolved fraction. In the salinity gradient, dissolved U, V, Mo exhibit conservative behaviour while Ni, Cu, As, Co and Cd showed additive behaviour suggesting desorption processes. In the surface sediment, metal concentrations are controlled by the particle-size, POC contents and Fe, Al and Mn – oxy(hydr)oxides. Calculated Enrichment Factor and Geoaccumulation Index evidenced As enrichment while the calculated mean effect range median quotients evidenced a low to medium ecotoxicological potential effects range in the surface sediments. Highlights: Trace metal transportation are controlled by SPM concentrations. Dissolved trace metal distribution vary in the salinity gradient. Ecotoxicological indexes in surface sediments show low to medium contamination.